2000
DOI: 10.4049/jimmunol.165.2.734
|View full text |Cite
|
Sign up to set email alerts
|

An Epithelial Cell Line That Can Stimulate Alloproliferation of Resting CD4+ T Cells, But Not After IFN-γ Stimulation

Abstract: It has previously been shown that IFN-γ-induced up-regulation of HLA class II on the surface of epithelial cells is not sufficient to induce proliferation of allospecific CD4+ T cells in vitro. To further investigate this phenomenon, a human epithelial bladder carcinoma, T24, was induced to constitutively express HLA class II without IFN-γ stimulation, by permanent transfection with the full-length class II transactivator (CIITA) gene. Proliferation of allospecific T cells to transfected and wild-type cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…These data make it unlikely that an anergy defect in T cells is responsible for making p21 -/-mice prone to lupus erythematosus [24][25][26]. Moreover, p21 -/-mice on a different background were not lupus-prone [38]. The defects of T and B cells leading to loss of self-tolerance in lupus are complex and have only partially been characterized [39].…”
Section: Discussionmentioning
confidence: 99%
“…These data make it unlikely that an anergy defect in T cells is responsible for making p21 -/-mice prone to lupus erythematosus [24][25][26]. Moreover, p21 -/-mice on a different background were not lupus-prone [38]. The defects of T and B cells leading to loss of self-tolerance in lupus are complex and have only partially been characterized [39].…”
Section: Discussionmentioning
confidence: 99%
“…HLA-DR expression was induced in Eahy.926 by permanent transfection with the class II transactivator (CIITA) (19) or induced in aortic EC or human heart microvascular EC by interferon (IFN)-␥ pretreatment (20,21). HLA-DR-restricted CD4ϩ T cells that could proliferate to EC expressing the appropriate HLA-DR molecules are referred to as ECspecific T cells, and those that did not were termed third party T cells.…”
mentioning
confidence: 99%
“…cells were cultured in Dulbecco's modified Eagle's medium (Sigma, Dorset, UK) containing 10% FCS (Sigma) and 0.04% hypoxanthine, aminopterin, thymidine (Invitrogen, Paisley, UK) and passaged weekly. Eahy.926 that was permanently transfected with CIITA (EahyCIITA) (19) was cultured as described previously in this report, with 0.2 mg/mL geneticin (Invitrogen). Human aortic EC and human heart microvascular EC (HHMEC) were isolated from donor aorta or ventricle, respectively.…”
mentioning
confidence: 99%
“…This cell line has been shown to respond to cytokines and support transendothelial migration of leukocytes in a similar manner as primary endothelial cells (44). Untreated Eahy.926 do not express MHC class II (44), but MHC class II expression can be induced by permanent transfection with the MHC class II trans-activator CIITA (EahyCIITA) or by 4-day treatment of Eahy.926 with IFN-␥ (45). We have previously shown that transfection of Eahy.926 with CIITA induced MHC class II expression (DR13, DR11) whereas other molecules, including ICAM-1 and VCAM-1, which may be involved in transmigration, are not up-regulated (45).…”
mentioning
confidence: 99%
“…Untreated Eahy.926 do not express MHC class II (44), but MHC class II expression can be induced by permanent transfection with the MHC class II trans-activator CIITA (EahyCIITA) or by 4-day treatment of Eahy.926 with IFN-␥ (45). We have previously shown that transfection of Eahy.926 with CIITA induced MHC class II expression (DR13, DR11) whereas other molecules, including ICAM-1 and VCAM-1, which may be involved in transmigration, are not up-regulated (45). In this way we have been able to dissect the effects of MHC class II expression on T cell migration from other proinflammatory effects that might be mediated by IFN-␥.…”
mentioning
confidence: 99%